Doing shifts: the role of correctional officers - Franchi, Serena (Palgrave studies in prisons and penology, 2024)
Chapter 1. Introduction: From poverty governance to disciplinary practices in prison -- Chapter 2. Pervasive social control: How merit shapes authorities’ perception -- Chapter 3. Being correctional officer: Unattended expectations and coping strategies -- Chapter 4. Identifying as correctional officer: A relational factor -- Chapter 5. Acting as correctional officer: Authority trough discretion -- Chapter 6. Conclusion.